Partial knee replacement could be first choice for some patients with osteoarthritis. (30th December 2019) - Cook, Rob; Davidson, Peter; White, Alicia
The study: Beard D, Davies L, Cook J, et al. The clinical and cost-effectiveness of total versus partial knee replacement in patients with medial compartment osteoarthritis (TOPKAT): 5-year outcomes of a randomised controlled trial. Lancet 2019;394:746-56. The study was funded by the NIHR Health Technology Assessment Programme (project number 08/14/08). To read the full NIHR Signal, go to https://discover.dc.nihr.ac.uk/content/signal-000824/partial-knee-replacement-could-be-first-choice-in-some-patients